Everyday Stories for Everyday People: Communal Responsibility and Nepantla Literacies in Early Childhood Education. (July 2020) - Valdez-Gainer, Nancy; Gainer, Jesse
This article focuses on a teaching–research relationship between a teacher and a university professor who are a married couple. The article highlights how we navigated our relationship during a project with second graders with the hope of opening Third Space for students to engage in collective storytelling in an environment that interrupts mainstream hierarchies of power and authority and centers the Afrocentric pedagogy of communal responsibility. The story of the dyad relationship is woven into the stories of and from the children in what we view as nepantla literacies fostering collective agency and classroom consciousness.